KKM PPM-PEMANFAATAN TEKNOLOGI AKUAPONIK BUDIDAYA TANAMAN SAYUR-SAYURAN DAN IKAN DI PONDOK PESANTREN RIYADHUSSALAM DESA KURUNGKAMBING KECAMATAN MANDALAWANGI KABUPATEN PANDEGLANG BANTEN - Alimuddin, Alimuddin (Jurnal BALIRESO, 2019)
Pesantren is an Islamic-based education known in Indonesia in educating people's lives. There areproblems with the view of modern society towards the world of pesantren, which does not providehope for work. So it is demanded to be able to master religious and general sciences includingtechnology. Through the utilization of aquaponics technology for pesantren-based communities,Sultan Ageng Tirtayasa University (UNTIRTA) implements that the activities of Learning andCommunity Empowerment Real Work (KKN-PPM) is one of the activities that can improvestudents' ability to apply knowledge according to their respective fields of expertise, respectively.KKN-PPM provides opportunities for students to work together to contribute to solving problemsin the pesantren community. Therefore, KKN-PPM has a significant contribution and impact onstudents and the pesantren community. Therefore, KKN-PPM has a significant contribution andimpact on students and the pesantren community. The goals of the KKN-PPM achievements willbe held at Pesantren Riyadhussalam in Kurungkambing Village, Mandalawangi District, toimprove students' ability in applying science and technology in accordance with their fields ofscience and expertise, especially in the field of aquaponics with partner P4S MITRA IKAMAJAfor teaching Aquaponics technology to students. Methods the activity begins with providingdebriefing to KKN-PPM participants and then providing counseling, training, and application ofappropriate technology and assistance to further develop vegetable and fish plant productsproduced by pesantren communities. Thus, the implementation of KKN-PPM can create and toincrease the productivity of the pesantren community in building self-reliance in order to gainknowledge, skills, and a decent life, a sustainable Islamic Boarding School is formed.